ANALISIS TINGKAT VALIDITAS MEDIA BUKU BERGAMBAR “CALIS” BERBASIS KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BACA-TULIS SISWA ADHD DI SDN SIDOREJO II TUBAN - agustin, ina; Mubarokah, Shobihatul (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2023)
Children with ADHD are children with special needs who need special services and attention, especially in formal education. Children with ADHD or often called hyperactive experience difficulties in learning because of difficulty concentrating. The learning difficulties referred to are difficulties in reading and writing at the beginning. To overcome the difficulties he faces, it is necessary to use interesting media so that he can focus his concentration and make him more enthusiastic about learning so that he can improve his reading and writing skills. Researchers used the picture book